A systematic review of montmorillonite-asphalt composite materials: Green clay mineral-reinforced asphalt for sustainable pavement solutions - Hao Lai; Anhua Xu; Jianliang Zhai; Youjie Zong; Wei Deng; Haoyan Guo; Bowen Guan; Mingfeng Chang; Rui Xiong; Zhenjun Wang (Applied Clay Science, 2025)

Numerical Simulation Study on Ship–Ship Interference in Formation Navigation in Full-Scale Brash Ice Channels - Chang Xie; Li Zhou; Mingfeng Lu; Shifeng Ding; Xu Zhou (Journal of Marine Science and Engineering, 2023)
Formation navigation in brash ice channels is increasingly utilized by merchant vessels in the Arctic and Baltic Sea, offering benefits such as improved efficiency and reduced carbon emissions. However, ship–ship interference poses a significant challenge to this method, impacting resistance performance. This paper presents full-scale simulations using the CFD–DEM coupling method in brash ice channels, which is validated by comparing simulation results with ice tank measurements. By varying the distance between two ships from 0.05 to 5 ship lengths, ship–ship interference in full-scale brash ice channels is analyzed using the CFD–DEM coupling strategy. The study examines hydrodynamic and ship–ice interactions, ice resistance effects, and simulation results. It is found that ship-to-ship distance significantly influences the velocity field, dynamic pressure distribution on the hull, and hydrodynamic interaction forces. Distances less than one ship length result in increased water resistance for the forward ship and decreased resistance for the rear ship. The forward ship demonstrates favorable interference with the ice accumulation of the rear ship. When distances are less than two ship lengths, the ice resistance of the forward ship remains mostly unaffected, while the ice resistance of the rear ship decreases as the distance decreases. These insights enhance our understanding of ship–ship interference in formation navigation, aiding in the optimization of brash ice channel navigation strategies.

Construction of a series of episomal plasmids and their application in the development of an efficient CRISPR/Cas9 system in Pichia pastoris - Yang Gu; Jucan Gao; Mingfeng Cao; Chang Dong; Jiazhang Lian; Lei Huang; Jin Cai; Zhinan Xu (World Journal of Microbiology and Biotechnology, 2019)

Advanced glycation end products promote proliferation and suppress autophagy via reduction of Cathepsin D in rat vascular smooth muscle cells - Mingfeng Ma; Xiaofan Guo; Ye Chang; Chao Li; Xin Meng; Si Li; Zhen-Xian Du; Hua-Qin Wang; Yingxian Sun (Molecular and Cellular Biochemistry, 2015)